Research methodologies in music education - Hartwig, Kay Ann (Cambridge Scholars Publishing, 2014)
This volume provides an understanding of various research methodologies that have been used in music education projects. These methodologies include: historical research; quantitative research; narrative inquiry; action research; ethnography; case study; interpretative phenomenological analysis; arts-based methods; and mixed methods. Each of these research methodologies is detailed, before examples of music education projects that have used these methodologies are described. A separate chapt ...